2020
DOI: 10.2147/idr.s262311
|View full text |Cite
|
Sign up to set email alerts
|

<p>Oral Prevalence of <em>Candida</em> Species in Patients Undergoing Systemic Glucocorticoid Therapy and the Antifungal Sensitivity of the Isolates</p>

Abstract: Background Candida species are commonly detected as colonizers of the oral cavity; candidiasis or candidemia can develop in patients who are immunocompromised. Use of topical or inhaled glucocorticoids can alter the spectrum of Candida species and can promote oral candidiasis. The present study aims to evaluate the diversity of Candida species in the oral cavity and their susceptibility to antifungal agents in patients undergoing treatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…isolated in people living with HIV with diabetes (50%). Other similar results (China and Iran) corroborate our results, with this species being the most or one of the most NCAC isolated (both in single and multi-fungal cultures) [ 55 , 56 , 57 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…isolated in people living with HIV with diabetes (50%). Other similar results (China and Iran) corroborate our results, with this species being the most or one of the most NCAC isolated (both in single and multi-fungal cultures) [ 55 , 56 , 57 ].…”
Section: Discussionsupporting
confidence: 90%
“…Previous research showed the effectiveness of Vcz and AmB Candida spp. isolates [ 25 , 26 , 55 , 58 , 59 , 60 , 61 , 62 ] (Portugal, Brazil, Korea, US, Japan), but also of both AmB and Flu (China) [ 57 ], as seen in this work. A recent study involving immunosuppressed patients (with diabetes mellitus), showed a predominance of C. albicans , but among denture wearers, C. glabrata was prevalent.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, the duration of corticosteroid therapy was greater in these patients compared to patients with OC caused by one Candida species. Similar to our findings, Xia et al reported corticosteroid therapy caused an increased prevalence of OC by non-albicans strains (Xiao et al, 2020). Moreover, Nambiar et al noted that the development of OC in COVID-19 patients could be due to prolonged mechanical ventilation in the ICU and the long-term use of broad-spectrum antibiotics.…”
Section: Discussionsupporting
confidence: 90%
“…For example, a study reported 85% fluconazole susceptibility in 2013, while in 2020, 48% susceptibility was reported against C. glabrata [ 18–21 ]. Likewise, a study for C. parapsilosis in 2012 reported 98.6% susceptibility, while 76.93% susceptibility was reported in 2020 against itraconazole [ 22 , 23 ]. Likewise, a study in 2014 reported 100% itraconazole susceptibility rate against C. krusei , while in 2016, a study reported 16.7% susceptibility rate [ 24 , 80 ].…”
Section: Discussionmentioning
confidence: 99%